Experiential Learning dan Daur Belajar sebagai Metode Belajar Berbasis Pengalaman - Nugrahening Pinasti, Anisa (Perpustakaan Universitas Gadjah Mada, 2023)
This research aims to find out the concept of learning methods in Sanggar Anak Alam (SALAM), namely Learning Cycle and experiential learning by David A. Kolb. The research method used is the literature study method of research related to experiential learning and learning cycle method. The research results of the Learning Cycle method and experiential learning are interrelated, both learning methods center on how the experience of students can be generated as a process of the birth of knowledge. The learning cycle is carried out repeatedly in sequence from the start of learners experiencing, expressing, analyzing, concluding, and applying until learners can achieve their own knowledge. The freedom given by SALAM in achieving knowledge becomes a means for learners to freely experiment, explore, and express.